Analisa Harmonisa Pada Unit Crane RTG (Rubber Tyred Gantry) Di PT. Nilam Port Terminal Indonesia - Choirul Anam; Nasyith Hananur Rohiem; Riny Sulistyowati (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2023)
RTG (Rubber Tyred Gantry) Crane tends to have harmonic distortions. It is caused by the VSD switching process that converts current from DC to AC, decreasing the power quality and affecting power generation. Disturbance tends to happen on voltage or a current sine wave of the system that contains multiplied frequency from fundamental frequency. It is required to analyze based on the IEEE standard of Std 519-2014 which described that the 20kV bus voltage has a limit value of 3% for VIHD and 5% for VTHD. By using available software, simulation is applied to the RTG Crane electrical system. Harmonic distortion will be discussed by gathering simulation result data in the form of the harmonic spectrum and harmonic wave. harmonic filter to be applied is an Active Filter and Passive Filter that then compared the compatibility to solve the harmonic distortion. The analysis is also applied to Power Factor (PF) value changes before and after filter installation.